DESIGN AND ANALYSIS OF BUILDING CONSTRUCTION WITH EQUIPMENT GREEN ENERGY POWER PLANT BY HOMER METHOD - Tachrir, Tachrir (Fakultas Teknik Jurusan Sipil Universitas Halu Oleo, 2023)
Technology has been able to make a power generation system by utilizing solar radiation into electrical energy in the form of PLTS (Solar Power Plant). This article aims to design an off grid PLTS Building and Equipment’s with a capacity of 88 kWp to meet the electricity needs of the people of Kogholifano Village, Pasir Putih District, Muna Regency. Analysis of the performance of 88 kWp off grid solar power plant in kogholifano village was simulated using Software HOMER. The design of the PLTS begins by analyzing the existing 40 kWp PLTS of Kogholifano village. The technical and financial performance of the 88 kWp off-grid solar system was simulated via HOMER. The results of the analysis show that this system will provide electrical energy supply with an operating time of 24 hours / day